SUDHA MURTHY…..A MIND BLOWING EDUCATIONIST N NOVELIST - Shushma Raj Choudhary (IJRDO - Journal of Social Science and Humanities Research, 2026)
Sudha Murty is a highly acclaimed Indian author, educator, and philanthropist recognized for her immense contributions to children’s literature, social work, and for being a trailblazing engineer. Her work as an educationalist is characterized by a commitment to fostering literacy, establishing over 70,000 libraries in rural schools, and promoting moral values, compassion, and social responsibility. As a novelist and writer, she is celebrated for her simple, heartfelt, and relatable style in both Kannada and English, focusing on themes of human values, societal issues, and the experiences of ordinary people.